Reuse of Insulin Pens Among Multiple Patients at 2 Veterans Affairs Medical Centers. (22nd July 2015) - Schirmer, Patricia; Winston, Carla A.; Lucero-Obusan, Cynthia; Winters, Mark; Lesse, Alan; de Comarmond, Charles; Oda, Gina; Martinello, Richard A.; Holodniy, Mark
Abstract : OBJECTIVE: To determine whether reuse of insulin pens among multiple patients resulted in transmission of bloodborne pathogens (BBP). DESIGN: Retrospective cohort study. SETTING: Two Veterans Affairs medical centers. PATIENTS: Veterans who received insulin via insulin pens from 2010 to 2013. METHODS: Patients were identified through electronic health records, notified of possible exposure, and serotested for human immunodeficiency virus, hepatitis C virus (HCV), and hepatitis B virus. Newly discovered case patients were assessed in relation to potential proximate patients to determine viral strain relatedness by HCV envelope ( env ) gene sequencing. RESULTS: Of 1, 791 hospitalized veterans who received insulin via insulin pen, 1, 155 were tested for at least 1 viral infection after exposure. Of these, 67 patients were newly diagnosed with 1 or more viral BBPs. For human immunodeficiency virus and hepatitis B virus no additional strain testing of case or proximate patients was possible; 8 HCV cases and 45 proximates (40 unique patients; 5 patients were positive for 2 genotypes) were identified as needing strain testing. Only 3 cases and their 19 proximates had samples available for further testing. None of the 26 remaining proximate patients had blood available for further testing. Median genetic distance between the HCV env sequences of those available for additional testing ranged from 14% to 24%, indicating nonrelatedness. CONCLUSIONS: Our investigation revealed that exposure to insulin pen reuse did not result in HCV transmission among patients who had viral genetic analysis performed. Analysis for any additional potential transmission of blood-borne pathogens was limited by the available samples. Infect Control Hosp Epidemiol 2015;36(10):1121–1129